Upaya Guru Pendidikan Agama Islam Dalam Meningkatkan Religiusitas Siswa Di Smk Muhammadiyah 3 Nogosari Tahun 2015\2016 - Afifah, Nur, Dr. Syamsul Hidayat, M.Ag (2016)
Educationis an activity which must be conducted by human, because by the existence of education, human can think smart, especially the religious education which has an important role in forming the character and increasing someone's religiousity. In this matter, a teacher has a role in increasing the students' religiousity through many ways, either being directly implemented or through learning. Therefore, the writer was interested in researching more deeply by proposing a title "Efforts of The Islamic Religious education Teacher in Increasing The Students'Religiousity in Sekolah Menengah Kejuruan (SMK/Vocational High School) Muhammadiyah 3 in Nogosari Sub-district in 2016 In this research, the problem is the efforts of Islamic religious education teachers in increasing the students' religiousity in SMK Muhammadiyah 3 Nogosari. The objectives of this research are to know the efforts of the Islamic religious teachers in increasing the students' religiousity in SMK Muhammadiyah 3 Nogosari and the supporting factors as well as the inhibiting factors faced by the Islamic religious teachers in increasing thestudents'religiousity in SMK Muhammadiyah 3 Nogosari. The benefits of this research are that it could give a positive contribution for the school as well as the teachers in maintaining the good things and continuing in conducting evaluation to the students. This research is aqualitativeresearchwhich has taken place in SMK Muhammadiyah 3 Nogosari. The method of data collection uses an observation, documentation, and interview. Meanwhile, the data analysis uses the descriptive qualitative analysis through an inductive way: data collection, data display, and drawing conclusion. Based on the results of the data analysis, it could be concluded that: The Islamic religious education techers in increasing the students religiousity in SMK Muhammadiyah 3 Nogosari have efforts such as reciting Al-Qur'an together, conducting dhuha praying together or alone, holding a Sunday morning proselytizing, participating in Islamic holidays for examples, Idul Fitri praying and Idul Adha praying which are held in the school, and participating in the activities of social services such as distributing zakat to poor society, not eating illegitimate food, keeping away deed of shirk, participating in praying and wraping the corpse. Such efforts has run well because the Islamic religious education teachers in SMK Muhammadiyah has implemented theories on the increasing of the student's religiosity maximally.